The Effect of Digital Leadership Style on Employee Performance with Organizational Commitment as an Intervening Variable at the Regional Financial and Revenue Management Agency of Binjai City - Fitri Ulyani Nasution; Abdi Sugiarto; Hernawaty (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study examines the effect of digital leadership style on employee performance with organizational commitment as an intervening variable at the Regional Financial and Revenue Management Agency of Binjai City. A quantitative research design was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Data were collected through structured questionnaires and analyzed by evaluating both the measurement and structural models. The measurement model results indicate that all indicators meet the criteria for convergent validity, with outer loading values exceeding 0.70, while discriminant validity is confirmed through cross-loading analysis. Reliability testing demonstrates strong internal consistency, as Cronbach’s Alpha values range from 0.790 to 0.915, composite reliability values exceed 0.876, and Average Variance Extracted (AVE) values are above 0.50 for all constructs. The structural model shows high explanatory power, with adjusted R² values of 0.938 for employee performance and 0.738 for organizational commitment. Hypothesis testing reveals that digital leadership style has a positive and significant effect on employee performance (β = 0.594, t = 8.077, p < 0.001) and organizational commitment (β = 0.861, t = 31.039, p < 0.001), while organizational commitment also significantly influences employee performance (β = 0.410, t = 5.908, p < 0.001). Furthermore, organizational commitment is found to significantly mediate the relationship between digital leadership style and employee performance (β = 0.353, t = 5.450, p < 0.001), highlighting the critical role of digital leadership and organizational commitment in enhancing employee performance within public sector institutions.